Development of Ready-to-fry Crab Products - C.V., Raju; N., Bhaskar; S., Dhananjaya (Fishery Technology, 2025)
Crabs are one of the major components of seafood industry in the world. This study contains the development of two important ready to fry products from crab meat viz., crab sticks and crab cutlets. The suitable recipes for these products are standardized and their chemical analysis recorded.